Residents' attitudes to tourists visiting their mosques: a case study from Istanbul, Turkey. Issue 1 (1st January 2018) - Egresi, István O.; Kara, Fatih
ABSTRACT: Resident perception of tourism impacts has been one of the most studied areas of tourism. However, there is an extremely limited literature on resident perceptions of religious tourism development, especially in non-Western countries. This study investigated the attitudes of local residents toward tourists visiting four important mosques in Istanbul, Turkey and their perception of religious tourism development. All residents surveyed were practicing Muslims who prayed in a mosque at least once a year. We found that, in general, local residents are supportive of tourists visiting their mosque, but the level of support may differ based on the demographic and cultural background of the residents as well as on the number of tourists visiting the mosque.